Elements of modern X-ray physics - Nielsen, J Als (Wiley, 2013)
Although the book has been written from the perspective of two physicists, we hope that it will be useful to the wider community of biologists, chemists, material scientists, etc., who work at synchrotron radiation facilities around the world